Knockdown of LncRNA GHET1 suppresses prostate cancer cell proliferation by inhibiting HIF‐1α/Notch‐1 signaling pathway via KLF2. (4th January 2019) - Zhu, Yanfeng; Tong, Yue; Wu, Jianhua; Liu, Yuejuan; Zhao, Mingjia
Abstract: Prostate cancer (PC) is one of the most common cancers in male groups worldwide. Long noncoding RNAs (LncRNAs) are reported to be dysregulated in a variety of cancers, including PC. This study aimed to explore the role of LncRNA GHET1 in the pathogenesis of PC. RT‐qPCR was carried out to examine the relative expression level of GHET1 in PC patients. In vitro, GHET1 siRNA (si‐GHET1) was used to investigate the biological role of GHET1 in PC cell lines. Cell proliferation was detected by CCK‐8 and colony formation assay, while cell cycle and cell apoptosis were analyzed using flow cytometry. Moreover, western blot was carried out to measure the protein expression levels of KLF2 and HIF‐1α/Notch‐1 signal pathway. We found that GHET1 showed higher expression in PC tissues and had a negative correlation with KLF2 expression. Knockdown of GHET1 significantly suppressed the cell proliferation, induced cell cycle arrest at G0/G1 phase and promoted cell apoptosis. Additionally, si‐GHET1 transfection induced KLF2 upregulation and HIF‐1α/Notch‐1 signal pathway suppression, which could be rescued by si‐KLF2 transfection. These results suggest the key role of GHET1 in PC progression. Moreover, GHET1 might be explored to be a potential target for clinical treatment of PC. © 2019 BioFactors, 45(3):364–373, 2019